Two Rare Variants in PLAU and BACE1 Genes—Do They Contribute to Semantic Dementia Clinical Phenotype? - Katarzyna Gaweda-Walerych (MDPI AG, 2021)
We have performed whole-genome sequencing to identify the genetic variants potentially contributing to the early-onset semantic dementia phenotype in a patient with family history of dementia and episodic memory deficit accompanied with profound semantic loss. Only very rare variants of unknown significance (VUS) have been identified: a nonsense variant c.366C>A/p.Cys122* in plasminogen activator, urokinase (PLAU) and a missense variant c.944C>T/p.Thr315Met in β-site APP-cleaving enzyme 1 (BACE1)—along with known disease-modifying variants of moderate penetrance. Patient-derived fibroblasts showed reduced PLAU and elevated BACE1 mRNA and protein levels compared to control fibroblasts. Successful rescue of PLAU mRNA levels by nonsense-mediated mRNA decay (NMD) inhibitor (puromycin) confirmed NMD as the underlying mechanism. This is the first report of the PLAU variant with the confirmed haploinsufficiency, associated with semantic dementia phenotype. Our results suggest that rare variants in the PLAU and BACE1 genes should be considered in future studies on early-onset dementias.